Analysis of Battery Energy Storage Capacity on Load Operating Duration in a 50 WP Portable Solar Power System - Bona Valti Marpaung; Erpandi Dalimunthe; Haris Gunawan (Sean Institute, 2026)
Limited access to electrical energy in remote areas requires alternative energy solutions, one of which is a portable solar power system (PLTS). One of the key components affecting system performance is the battery, which functions as energy storage.This study aims to analyze the effect of battery energy storage capacity on the duration of load usage in a 50 Wp portable solar power system. The research method used is experimental, including system design, component selection, assembly, and performance testing. The system consists of a 50 Wp solar panel, MPPT solar charge controller, 12 V 20 Ah battery, inverter, and LED load. Testing was conducted by observing battery voltage and load operating duration. The results show that the battery is capable of supplying a load of 35 W for approximately ±6 hours. The system operates stably with gradual voltage decline. Therefore, battery capacity significantly influences the duration of load usage.